Design of the FP-RESTORE study: a protocol for prospective, observational study of real-world treatments with endovascular therapy in patients with femoropopliteal artery Tosaka III in-stent restenosis - Qiang Li; Xu Li; Xin Fang; Meng Ye; Min Zhou; Zhenyu Shi; Hongfei Sang; Yong Ding; Ziheng Wu; Zibo Feng; Lianrui Guo (BMJ Open)
Introduction Femoropopliteal artery in-stent restenosis (FP-ISR) represents one of the main obstacles for stent implantation in peripheral artery disease patients, especially Tosaka III FP-ISR, which is also referred to as in-stent occlusion. Diverse endovascular treatments of Tosaka III FP-ISR are available, and the results are unequivocal. However, real-world data are limited. This study aims to evaluate the efficacy, safety and health economics evaluation of various endovascular procedures in the treatment of Tosaka III FP-ISR.Method and analysis This study is a prospective, multicentre, real-world, observational clinical study. Patients diagnosed with Tosaka III FP-ISR and treated with endovascular procedures in nine centres from 1 April 2021 to 31 December 2022 will be recruited. The relevant clinical information, Ankle-Brachial Index and CT angiography will be collected. All the participants will undergo follow-up at 1, 6, 12, 18 and 24 months after the operation. The primary outcome is freedom from clinically driven target lesion revascularisation at 24 months. Safety and health economics issues will also be reported.Ethics and dissemination The FP-RESTORE clinical trial has been registered at ClinicalTrials.gov (http://clinicaltrials.gov/). This study was also approved by the Institutional Review Board and Human Research Ethics Committee of Zhongshan Hospital, Fudan University (approval number: B2021-427). Moreover, written informed consent will be obtained at the time of recruitment. The study outcomes will be disseminated by publication in a peer-reviewed journal to provide information for further clinical practice.Trial registration number NCT04801004.